Three-dimensional Imaging Using the Electromagnetic Vortex Synthetic Aperture Radar - Kun LYU; Hui MA; Hongwei LIU (Leida xuebao, 2021)
The ElectroMagnetic Vortex (EMV) wave is named after the rotation around the wave propagation axis. This electromagnetic characteristic is called the Orbital Angular Momentum (OAM). Considering its azimuth angular resolution, this paper introduces the EMV wave into traditional Synthetic Aperture Radar (SAR) imaging and proposes a novel Three-Dimensional (3D) imaging scheme called EMV-SAR. In EMV-SAR, the echo is extended into 3D after involving the OAM mode domain. Based on the waveform diversity technology, the multiOAM-mode echo is obtained and simultaneously transformed into azimuthal angular signals via Fourier Transform (FT) to form the 3D data of range-azimuth-angular. In this study, we propose a joint two-dimensional azimuthal compression algorithm to generate 3D target imaging based on Radon FT. The simulation results validate the performance of the proposed system and algorithms and demonstrate the superiority of EMV-SAR in 3D imaging.